Turfs and timbers: Resource use in the construction of a Viking Age ring fortress - Mortensen, Morten Fischer; Baittinger, Claudia; Christensen, Jonas; Nielsen, Anne Birgitte; Nielsen, Søren; Pihl, Anders; Prøsch-Danielsen, Lisbeth; Ravn, Morten; Sindbæk, Søren Michael; Ulriksen, Jens (Danish Journal of Archaeology, 2022)
Viking Age ring fortresses were some of the largest construction projects in Danish prehistory. In this article we reconstruct the amount of turf and timber used in the construction of the Borgring ring fortress and estimate the resource area needed to supply the building materials. Using REVEALS pollen data modelling, we quantify the regional oak land cover and estimate the resource area. The results show that even though Borgring was built in an open cultural landscape, sufficient supply of oak for the construction would have been accessible within a few kilometres from the fortress.